Surface-potential-based drain current model for two-dimensional organic TFTs using the multiple trapping and release conduction theory. (January 2022) - He, Hongyu; Liu, Yuan; Tan, Yuyu; Wang, Xinlin; Lin, Xinnan; Zhang, Shengdong
Highlights: Surface-potential-based drain current model for two-dimensional confined conduction. The model using the carrier multiple trapping and release conduction theory. Description of the Arrhenius temperature characteristics of the drain current. Estimation of the density of trap states for the organic TFTs. Abstract: A new analytical surface-potential-based drain current model is presented for the organic thin-film transistors (TFTs) when carriers are confined in two dimensions. Following the carrier multiple trapping and release (MTR) conduction theory, i.e., the assumption that the trapped carrier concentration is much higher than the free carrier concentration, the model is developed. The presented model can account for the linear regime and saturation regime by a single formulation. The calculated results of the presented model are verified by the available experimental drain current considering the temperature characteristics. Comparing with the previous model using the variable range hopping and percolation (VRH) conduction theory, although the presented model and the previous model are similar in mathematics, the presented model is more efficient to estimate the density of trap states for the organic TFTs.